Caracterización del síndrome del agotamiento psicológico en profesores universitarios de América Latina: una revisión bibliográfica - Mahecha-Naranjo, Gina; Álvarez-Alucema, Leandro Efrain; Campo-Torregrosa, Yelis; Caballero-Olivares, Tirza; López-Sepúlveda, Rubén (Duazary, 2023)
Introduction: Teaching requires dedication, time, and mental work due to the diversity of tasks that must be carried out, which can generate burnout (psychological exhaustion). However, reviews of the characteristics of burnout in Latin American university professors still need to be discovered. Objective: To characterize psychological exhaustion in university professors in Latin America. Method: A bibliographic review of original studies was conducted from different sources in Spanish, English, and Portuguese with the keywords work stress, burnout, psychological exhaustion, teaching, and university professors. The frequencies of the characteristics of the dimensions of psychological exhaustion were described. Results: Eleven investigations showed that depersonalization mainly manifests burnout (up to 90%). Emotional exhaustion and low personal fulfillment reached up to 82%. Conclusions: Burnout among university professors manifests mainly with depersonalization. New systematic reviews should summarize the variables associated with psychological exhaustion in Latin American university professors.